L-carnitine Supplementation Enhances Nuclear and Cytoplasmic Maturation Rates of Sheep Oocytes In Vitro - Z. W. Bhakty; E. M. Kaiin; N. W. K. Karja; M. A. Setiadi (Tropical Animal Science Journal, 2021)
The aim of the present study was to determine the effectiveness of l-carnitine (LC) supplementation on nuclear and cytoplasmic maturation rates of sheep oocytes. In experiment 1, oocytes were maturated for 24 hours in tissue culture medium 199 supplemented with LC at doses of 0.3 mg/mL, 0.6 mg/mL, and 0.9 mg/mL. In experiment 2, oocytes were maturated and fertilized in a media supplemented with LC at a dose of 0.3 mg/mL and incubated with 5x106 sperm/mL for 12 hours. The treatment group consisted of LC supplementation only in maturation medium (P1), only in fertilization medium (P2), and in both maturation and fertilization media (P3). In experiment 3, sperm motility patterns were assessed using CASA after being exposed to fertilization medium supplemented with LC at a dose of 0.3 mg/mL for 0 and 3 hours. Our results showed that supplementation of LC at a dose of 0.3 mg/mL significantly (p<0.05) increased the percentage of oocytes reaching metaphase II (86.7±4.1%) compared to those supplemented with LA at doses of 0, 0.6, and 0.9 mg/mL (73.6±1.2, 81.4±1.3%, and 70.5±1.6%, respectively). The LC treatment in the fertilization medium only did not influence the number of two pronuclear formations (62.1±2.5%) compared to supplementation either in the maturation medium only (72.0±4.7%) or a combination of both in maturation and fertilization media (68.2±2.7%) (p<0.05). Further results after 3 hours of incubation compared to the control group showed the total motility (24.8±2.04% vs. 17.49±2.37%), progressive motility (14.17±2.03% vs. 6.49±1.64%), and curvilinear velocity (VCL) (119.70±3.73% vs. 71.15±10.59%) (p<0.05) were increased in the fertilization medium containing LC but it did not improve the fertilization rate. It is concluded that supplementation of LC at a dose of 0.3 mg/mL in the maturation medium only could better improve the nuclear and cytoplasmic maturation rates of sheep oocytes.